Post-translational modifications and immune responses in liver cancer - Wang, You-Wei; Zuo, Jia-Chen; Chen, Chong; Li, Xiao-Hong (Frontiers in Immunology, 2023)
Post-translational modification (PTM) refers to the covalent attachment of functional groups to protein substrates, resulting in structural and functional changes. PTMs not only regulate the development and progression of liver cancer, but also play a crucial role in the immune response against cancer. Cancer immunity encompasses the combined efforts of innate and adaptive immune surveillance against tumor antigens, tumor cells, and tumorigenic microenvironments. Increasing evidence suggests that immunotherapies, which harness the immune system's potential to combat cancer, can effectively improve cancer patient prognosis and prolong the survival. This review presents a comprehensive summary of the current understanding of key PTMs such as phosphorylation, ubiquitination, SUMOylation, and glycosylation in the context of immune cancer surveillance against liver cancer. Additionally, it highlights potential targets associated with these modifications to enhance the response to immunotherapies in the treatment of liver cancer.